DETERMINATION OF GLYCOSYLATED HEMOGLOBIN REFERENCE RANGE IN ADULT POPULATION ATTENDING A MILITARY CARE SET UP IN RAWALPINDI - Ali, Syed Khawar; Khan, Dilshad Ahmed; Khan, Farooq Ahmed (Pakistan Armed Forces Medical Journal, 2011)
Objective: To determine the glycosylated hemoglobin reference range in healthy adult population attending a military care setup in Rawalpindi in accordance with National Glycohemoglobin Standardization Program (NGSP) and International Federation of Clinical Chemistry (IFCC) Study Design: Descriptive cross-sectional study Place and Duration of Study: Armed Forces Institute of Pathology Rawalpindi from May - Oct 2010 Subjects and Methods: A total of 254 healthy adults (18-80 years) comprising 169 males and 85 females, were included by non probability consecutive sampling from Rawalpindi. History and clinical examination were carried out. Blood HbA1c was analyzed high performance liquid chromatography on biorad D-10. Data were analyzed by SPSS-17. Results: Total 254 subjects consisting of 169 males and 85 females were recruited from Rawalpindi Pakistan. The reference range of total population was found 4.6–6.56% and 2.69–4.81 mmol/mol in accordance with NGSP and IFCC, respectively. When compared in gender, HbA1c levels were not significantly changed. However, the healthy elderly population had higher HbA1c levels. Reference range for HbA1c based on NGSP in individuals <40 years was found 4.52-6.4% while for individuals aged > 40 years, it was 4.8-6.68%.. Conclusion: The reference ranges for healthy individuals and the recommended values for optimal therapy in diabetic patients have to be revised and adjusted. Population based reference ranges should be established to provide better patient care services.